PERAN KESELAMATAN PASIEN DALAM MUTU PELAYANAN KESEHATAN DI PUSKESMAS - Dewi Sumbang Rorosati; Candra Dewi Rahayu; Siti Khoiriyah; Fifi Alviana (Fakultas Ilmu Kesehatan (FIKES) Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
Background: Patient safety is an important issue in maintaining and improving the quality of nursing services. Efforts to improve quality can be made by implementing risk management and patient safety in every health service setting, including at the Community Health Center. Objective: to determine the relationship between patient safety implementation and the quality of health services at the Public Health Center Research method: This used a descriptive analytical method with a cross sectional study approach. The total population is 36 nurses in 2 Public Health Center. The sampling technique is total sampling. The research instrument uses an instrument that has been tested for validity and reliability by bivariate analysis using the Spearman test. Research results: there is a relationship between the implementation of patient safety and the quality of health services at the health center with a p value of 0.000 < 0.05. Conclusion: Patient safety is an important thing to implement in Community Health Centers to maintain and improve the quality of service in that setting. So it is important for health workers to provide health services in accordance with patient safety standards.